2020
DOI: 10.1097/yic.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in patients diagnosed with tramadol dependence compared to healthy controls

Abstract: Cognitive impairment is one of the consequences of substance use. We aimed to estimate the prevalence and correlates of cognitive impairment among patients with tramadol dependence in comparison with healthy controls. The sample consisted of 30 patients with tramadol dependence and 30 healthy controls. Cognitive functions were assessed using Benton Visual Retention Test- revised, Trail Making Test A and B and Wechsler Memory Scale. Patients were also subjected to the Structured Clinical Interview for diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…Zakaryaee et al, (2012) found significant differences between the performance of tramadol-dependent patients and controls on the Wisconsin Card Sorting Test ('the paper test'), especially regarding categories completed and preservative errors. Using Trail Making Test Form B, Elrassas et al, (2021) found poor performance of tramadol-dependent patients in comparison to controls, which is in agreement with the present study.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Zakaryaee et al, (2012) found significant differences between the performance of tramadol-dependent patients and controls on the Wisconsin Card Sorting Test ('the paper test'), especially regarding categories completed and preservative errors. Using Trail Making Test Form B, Elrassas et al, (2021) found poor performance of tramadol-dependent patients in comparison to controls, which is in agreement with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, tramadol-dependent patients showed some impairment in visuospatial memory when compared to controls. This is in agreement with Elrassas et al, (2021), who found that tramadol-dependent patients showed significantly lower performance of visual memory using the Benton Visual Retention Testrevised. In this study, no significant difference was found between tramadol and control groups regarding attention using the Go/No-Go PEBL test, although the control group's scores were generally better.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations